Solar cycle and annual variations of Sq(H) at Alibag - Yacob, A.; Rao, D. Radhakrishna (My University, 1966)
A study of the amplitudes and phase angles of the first two harmonics of the monthly Sq(H) at Alibag with respect to solar activity (sunspot number, R), for the period 1905–1960, shows that (1) the amplitudes of both the harmonics have high positive correlations with R, (2) the phase angle of the first harmonic is negatively correlated with R, but with rather low correlation coefficients (3) the phase angle of the second harmonic is uncorrelated with R. These findings confirm the earlier results obtained with annual mean values. Monthly linear regression equations are given for R and the amplitudes and phase angles. Annual variations of the amplitudes and phase angles, as well as those of the coefficients in the monthly linear regression equations, are shown for the entire period of the investigation and also for the solar maximum and minimum epochs. The annual variations of the phase angles show large changes for the latter half of the year with sharp minimum in September and maximum in November. These changes are similar for both the harmonics and the magnitudes as well as the character are the same for the solar maximum and minimum epochs, suggesting atmospheric tidal origin for the phenomenon.
Keywords: Annual variation; Solar activity; Solar cycle; Alibag